Pancasila dan keadilan hukum - qohrunnada widodo, Aulia ainus safina (Maliki Interdisciplinary Journal, 2025)
Pancasila as the foundation of the Unitary State of the Republic of Indonesia has an important role in the formation of the legal system in Indonesia. As a state ideology, Pancasila is not only a normative guideline, but also directs the implementation of law to create social justice. The noble values ​​contained in Pancasila, such as justice and substantive procedures, provide a foundation for law enforcement that is fair, equitable, and in accordance with humanitarian principles. However, the application of Pancasila in the legal system faces various challenges, including corrupt practices, legal inequality, and low public legal awareness. This article discusses the role of Pancasila in building legal justice in Indonesia and strategic efforts to overcome these challenges. The conclusion drawn is the importance of collective commitment from the government, law enforcement officers, and the community in implementing the values ​​of Pancasila to create a just and equitable legal system.